Correlation of religious coping strategy with quality of life of the elderly with colorectal cancer referred to colorectal clinics of Shahid Beheshti University of Medical Sciences - Esmaeili, Roghayeh; Mohammadi , Mostafa; Madadi, Mansoureh; Fani, Mahdi (Advances in Nursing & Midwifery, 2022)
Background: Among the types of cancers, colorectal cancer is more likely to occur in the elderly; It is known as one of the most common causes of death in the world. Cancer and living with an ostomy affect different aspects of the elderly life and increase stress in them. Religious coping strategies are methods based on spirituality and religion that help a person deal with stressful issues so that patients can adapt to the situation by increasing acceptance. Objectives: The aim of this study was to investigate the correlation between religious coping strategies and quality of life in elderly patients with ostomy colon cancer Methods: This study was a descriptive_correlational which was carried out on 85 elderly patients with colon cancer who referred to colorectal clinics of Shahid Beheshti University of Medical Sciences hospitals in 2019. The inclusion criteria were the diagnosis of colon cancer by the oncologist, having an abdominal ostomy, age of sixty years and older, lack of cognitive impairment by MMES (Mini Mental Examination Status) and passing at least six-month of ostomy. Sampling method was convenience. The data collection tool was persian version of Pargament's Brief religious coping Scale and the City of Hope quality of life-ostomy questionnaire. Chi-square, independent t-test, Pearson correlation and linear regression models were used to analysis. Results: The results showed that the mean age of patients was 65.28 years. The mean score of quality of life was 232.58 with standard deviation of 41.17. The mean score of religious coping was 30.55 with standard deviation of 3.19 . The correlation between quality of life and religious coping was seen and there were positive and significant correlation between religious coping and spiritual of quality of life (r=0.269, p=0.001). Conclusion: There was a direct and significant correlation between health dimentional of quality of life and religious coping strategies. Healths care providers with focus on coping skills training and strengthening religious coping styles in routine care can improve the quality of life of these patients.